Youth Political Strategy in Political Contestation in 2014 Legislative Electio - Adela, Febriza Rizky; Arifin, Adil; Adela, Fernanda Putra (Talenta Publisher, 2019)
Not many young people actively participate in or take part directly in political contestation and become part of the success of winning the contest. In this paper, it reveals the strategies of the youth to win political contestation and become a member of the DPRD of Medan City for the period 20142019, within the scope of a democratic system and succeeded in becoming one of the elected parts to represent the community in the regional legislature. The purpose of this paper is to encourage more democratic political development in increasing the participation of young groups in developing their regions. The methodology used in this paper is a qualitative approach that produces descriptive data.